Users’ Expectations Towards ICT Infrastructure and Library Services of Rabindra Library: A Study on PG Students and Research Scholars of Assam University, Silchar (LIS TODAY, 2023)
The progressive advancement of technology, the overflow of information, the unpredictable  and unlimited wants of information, the hike of the price of information and the limited  capital in the library are the huge challenges modern library is encountering. But despite all  those challenges libraries are putting an energy and effort to cope with the challenges.  Library provide many services, procure many modern ICT Infrastructure to provide the  users the resources they want at the most conveniences and expectation. Understanding the  users’ expectations is not that easy as the conception we have. Therefore, this study is  conducted to understand the library user’s expectation on ICT infrastructures and library  services taking PG Students and Research Scholars of 16 (sixteen) departments of Assam  University Silchar, the study area selected by purposive method.
Keywords: Users expectations; Information Seeking Pattern; ICT Infrastructure; Library Services; Rabindra Library- Assam University; Silchar